Going around in circles: deciphering the role of circular RNAs in neurodegenerative disease. Issue 2 (March 2020) - Kondo, Mari A.; Mohan, Adith; Mather, Karen A.
Abstract : Purpose of review: Circular RNAs are highly expressed in the brain, accumulate with ageing and may play important functional roles. Hence, their role in age-related neurodegenerative diseases, including Alzheimer's disease and Parkinson's disease, is under active investigation. This review provides an overview of our current knowledge regarding the roles of circular RNAs in Alzheimer's disease and Parkinson's disease. Recent findings: More studies have examined Alzheimer's disease than Parkinson's disease. Circular RNA 7 ( ciRS-7 ) has been implicated in both diseases and may play a causative pathological role in at least Alzheimer's disease. The identification of circular RNA interaction networks is a primary focus. However, different analysis pipelines can generate quite disparate results, hence bioinformatically identified candidate circular RNAs require experimental and functional validation. Summary: Although this field of research is in its infancy, rapid advances holds promise for identifying circular RNAs that are important in neurodegenerative diseases. CiRS-7 is a promising candidate for further examination. More studies are required focussing not only on Alzheimer's disease and Parkinson's disease but also on other neurodegenerative diseases. Whether circular RNAs can be used to inform diagnostic, prognostic and therapeutic strategies for age-related neurodegenerative disease remains unclear.